Slaveriets profitabilitet. Økonomi og moral i fransk melodrama om den haitianske revolution, 1792-1798 - Kjærgård, Jonas Ross (Passage - Tidsskrift for litteratur og kritik, 2014)
Jonas Ross Kjærgård: “The Profitability of Slavery. Economy and Morals in French Melodrama on the Haitian Revolution, 1792-1798” This article investigates how French revolutionary melodrama depicted the institution of slavery after the outbreak of the Haitian revolution in 1791. Prior to the slave rebellion in France’s most important Caribbean colony, St.-Domingue (present day Haiti), abolitionary writers and intellectuals had presented the argument that slavery was not only morally wrong but also economically unprofitable. For the more radical writers of the 1770s, such as Abbé Raynal and Louis-Sébastien Mercier, slavery was an evil that called for revolutionary violence in the colonies. However, when news of the actual slave revolt and its violent incidents reached France, the stance on violence and the interconnection of morals and economy changed. Through a reading of three plays the article aims to show that the Haitian revolution – as well as the radicalization of the French revolution – caused play writers to condemn violence among the slaves; to urge rebelling slaves to return to the plantations; and to present a colonial system in which slaves became free workers in return for their promise to work hard and accept the continuation of French colonial rule.